2016
DOI: 10.3389/fmicb.2016.01872
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling of Type II Toxin–Antitoxin Genes of Helicobacter pylori under Different Environmental Conditions: Identification of HP0967–HP0968 System

Abstract: Helicobacter pylori is a Gram-negative bacterium that colonizes the human gastric mucosa and is responsible for causing peptic ulcers and gastric carcinoma. The expression of virulence factors allows the persistence of H. pylori in the stomach, which results in a chronic, sometimes uncontrolled inflammatory response. Type II toxin–antitoxin (TA) systems have emerged as important virulence factors in many pathogenic bacteria. Three type II TA systems have previously been identified in the genome of H. pylori 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 84 publications
(120 reference statements)
1
29
0
Order By: Relevance
“…Our group recently reported that antibiotics affect the expression of virulence factors in H. pylori (Cardenas-Mondragon et al, 2016). Whereas the environmental conditions tested here mostly up regulated expression of the transcription regulators analyzed, exposure to different antibiotics resulted predominantly in gene repression ( Figures 3, 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our group recently reported that antibiotics affect the expression of virulence factors in H. pylori (Cardenas-Mondragon et al, 2016). Whereas the environmental conditions tested here mostly up regulated expression of the transcription regulators analyzed, exposure to different antibiotics resulted predominantly in gene repression ( Figures 3, 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported the transcriptional profiling of type II toxin-antitoxin genes under different environmental conditions (Cardenas-Mondragon et al, 2016). The type II antitoxins function as transcriptional repressors of their own expressions (Yamaguchi and Inouye, 2011) and also regulate the expression of other genes related with cellular functions such as biofilm formation, persistence, and the general stress response (Wang and Wood, 2011; Hu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations